Visual marketing and its influence on brand value: the Pacari case - Cabanilla Oña, Josue; Coello Castañeda, Jessenia; Aguilar Gálvez, William; Bonisoli, Lorenzo (mktDESCUBRE; Vol 1 No 20 (2022): Twentieth Edition (July - December)DO - 10.36779/mktdescubre.v1i20.768, 2022)
The objective of this research is to determine the influence of visual marketing through the website on the brand value of the Pacari company. This work analyzes factors related to web usability, visual harmony, visual marketing and brand value. This study has a quantitative approach, the results were obtained by applying surveys to a sample of 159 individuals in the city of Machala with the common characteristic of having purchased the product and visited the brand's website. The results of the research demonstrated in its entirety the positive and significant influence between web usability and visual marketing, visual harmony in relation to visual marketing and finally the influence of visual marketing on brand equity. The research is beneficial for managers and entrepreneurs who wish to improve their consumers' experience in a digital environment through the correct application of visual marketing on a website and its influence on brand equity.